Is exhaled breath temperature the new asthma inflammometer. (24th May 2012) - Hamill, LM; Ferris, KCA; Kapande, KM; McConaghy, LA; Shields, MD
Abstract : Exhaled Breath Temperature has been proposed by many studies as a new biomarker in asthma control. It is thought to be a different physiological characteristic to core temperature and has been shown to be higher in asthmatics than non-asthmatics. A previous study has shown that EBT correlates to Fractional Exhaled Nitric Oxide (FENO) in a small subset of mild asthmatics that did not have a recent infectious episode. However, the study population were subject to a number of strict conditions that we feel are not realistic to obtain in a busy clinic environment. Therefore, our aim in this study was to clarify the relationship of EBT to current measures of asthma control under normal clinic conditions. Our patients had a range of severity and were not excluded if they had current or recent infection. There were no restrictions placed on their physical activity or dietary intake on the morning of clinic. We compared EBT with the current markers of asthma control e.g. FENO, FEV1, Current BTS step, and FEV1/FVC ratio. We also compared EBT to clinician's blinded decision (e.g increase treatment, decreased treatment or no change) and between children on different medications. The devices used were both handheld; FENO (NOBreathTM, Bedfont, England) and EBT (XhaloTM, Delmedica, Singapore). All measurements were taken in clinic between 09:00 and 12:30. Cross sectional study with 140 patients aged 4-16 years attending outpatient asthma clinic from June 2010-Aug 2011. The Range of EBT was 27.4–35.16 (mean 32.94). There was no correlation between EBT and logFENO (r=0.08), FEV1 (r=0.13) or FEV1/FVC ratio (r=−0.1). There were also no association between EBT and BTS step (ANOVA p=0.13), decision (ANOVA p=0.81) or difference in those on inhaled corticosteroids versus those not (t-test p=0.3) EBT as measured using the XHalo device did not correlate with established measures of asthma control. Further research is required to determine whether its serial use in individual patients would be beneficial. Another question that needs addressed is whether EBT has got a clinical use as an "inflamometer" if it can only be used under strict conditions.